Down's-syndrome-related kinase Dyrk1A modulates the p120-catenin–Kaiso trajectory of the Wnt signaling pathway - Hong, Ji Yeon (Company of Biologists, 2012)
The Wnt pathways contribute to many processes in cancer and development, with β-catenin being a key canonical component. p120-catenin, which is structurally similar to β-catenin, regulates the expression of certain Wnt target genes, relieving repression conferred by the POZ- and zinc-finger-domain-containing transcription factor Kaiso. We have identified the kinase Dyrk1A as a component of the p120-catenin–Kaiso trajectory of the Wnt pathway. Using rescue and other approaches in Xenopus laevis embryos and mammalian cells, we found that Dyrk1A positively and selectively modulates p120-catenin protein levels, thus having an impact on p120-catenin and Kaiso (and canonical Wnt) gene targets such as siamois and wnt11. The Dyrk1A gene resides within the Down's syndrome critical region, which is amplified in Down's syndrome. A consensus Dyrk phosphorylation site in p120-catenin was identified, with a mutant mimicking phosphorylation exhibiting the predicted enhanced capacity to promote endogenous Wnt-11 and Siamois expression, and gastrulation defects. In summary, we report the biochemical and functional relationship of Dyrk1A with the p120-catenin–Kaiso signaling trajectory, with a linkage to canonical Wnt target genes. Conceivably, this work might also prove relevant to understanding the contribution of Dyrk1A dosage imbalance in Down's syndrome.